Agreement in the reporting of General Practitioner requested musculoskeletal radiographs: Reporting radiographers and consultant radiologists compared with an index radiologist. Issue 2 (May 2022) - Cain, G.; Pittock, L.J.; Piper, K.; Venumbaka, M.R.; Bodoceanu, M.
Abstract: Introduction: This study assessed the inter-observer agreement of reporting radiographers and consultant radiologists compared with an index radiologist when reporting General Practitioner (GP) requested musculoskeletal radiographs. The potential effect of discordant reports on patient management and outcome was also examined. Methods: Three reporting radiographers, three consultant radiologists and an index radiologist reported on a retrospective randomised sample of 219 GP requested musculoskeletal radiographs, in conditions simulating clinical practice. A speciality doctor in radiology compared the observers' reports with the index radiologist report for agreement and assessed whether any discordance between reports was clinically important. Results: Overall agreement with the index radiologist was 47.0% (95% CI, 40.5–53.6) and 51.6% (95% CI, 45.0–58.1) for the consultant radiologists and reporting radiographers, respectively. The results for the appendicular and axial skeleton were 48.6% (95% CI, 41.3–55.9) and 40.9% (95% CI, 27.7–55.6) for the radiologists, and 52.6% (95% CI, 45.2–59.8) and 47.7% (95% CI, 33.8–62.1) for the radiographers, respectively. The difference in overall observer agreement between the two professional groups with the index radiologist was not statistically significant (p = 0.34). Discordance with the index radiologist's reports was judged to be clinically important in less than 10% of the observer's reports. Conclusion: Reporting radiographers and consultant radiologists demonstrate similar levels of concordance with an index radiologist when reporting GP requested musculoskeletal radiographs. Implications for practice: These findings contribute to the wider evidence base that selected radiographers with appropriate postgraduate education and training are proficient to report on musculoskeletal radiographs, irrespective of referral source.